Minimal residual disease in multiple myeloma: use of magnetic resonance imaging - Hillengaß, Jens; Merz, Maximilian; Delorme, Stefan (Seminars in hematology, 2018)
The increasing percentage of patients achieving deep responses in multiple myeloma has led to the need for more sophisticated instruments to measure residual disease as a potential source of relapse. As minimal residual disease assessment is mostly performed on a bone marrow specimen from a certain area of the body, such samples have the limitation that they might not really represent the actual tumor burden, because focal accumulations of malignant cells might be either hit or missed. Magnetic resonance imaging is a highly sensitive technique for the assessment of tumor burden and can be performed as whole-body protocol, overcoming the problem of sampling error for minimal residual disease assessment. Despite its high sensitivity, however, magnetic resonance imaging cannot differentiate between vital and necrotic lesions after therapy. Therefore, new fusion and functional techniques are currently under investigation, and image-guided biopsies are performed to combine the strengths of all available methods.